TRANSFORMASI BIMBINGAN DAN KONSELING DAN IMPLIKASINYA BAGI PENDIDIKAN SEKOLAH DASAR - Nurhalisa, Siti; Sunarti, Titi; Vitrianti, Vivit; Aliyah, Putri Robiatul; Silvi, Silvi (Universitas Negeri Medan, 2025)
Guidance and counseling (BK), is a field of science that studies self-development, potential, problem solving, and decision-making in the individual itself with the guidance of a counselor / teacher. The first counseling guidance counseling was in America in the early 20th century, pioneered by Frank Parsons, known as the Father of